2016
DOI: 10.1021/acs.jpcc.6b00552
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies Engineering of Iron Oxides Films for Solar Water Splitting

Abstract: International audienceHematite (α-Fe 2 O 3) can be considered as one of the top candidates to act as photoanode in the framework of clean hydrogen production through solar water splitting. The O:Fe ratio, that in this material plays a crucial role in the definition of its photoelectrochemical properties, has been investigated in detail. For this purpose, we examined thermal magnetite oxidation and hematite reduction as two possible routes to produce semiconducting iron oxides layers with controlled stoichiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 39 publications
5
84
0
Order By: Relevance
“…It was demonstrated that the introduction of oxygen vacancies considerably increased the electrical conductivity. However, under these reducing condition precursor oxides can easily form magnetite (Fe 3 O 4 ) which is highly detrimental for photolysis as it is either metal‐like or behaves like a narrow band gap (<1 eV) semiconductor . In other words, it is desired to introduce oxygen vacancies into α‐Fe 2 O 3 while suppressing the formation of Fe 3 O 4 .…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…It was demonstrated that the introduction of oxygen vacancies considerably increased the electrical conductivity. However, under these reducing condition precursor oxides can easily form magnetite (Fe 3 O 4 ) which is highly detrimental for photolysis as it is either metal‐like or behaves like a narrow band gap (<1 eV) semiconductor . In other words, it is desired to introduce oxygen vacancies into α‐Fe 2 O 3 while suppressing the formation of Fe 3 O 4 .…”
Section: Introductionsupporting
confidence: 50%
“…Furthermore, literature generally describes that a thermal oxidative annealing leads to oxide layers that consist of a gradient of wustite (FeO), magnetite (Fe 3 O 4 ), and α‐Fe 2 O 3 . Since FeO and Fe 3 O 4 are either metal‐like or behave like a narrow band gap (<1 eV) semiconductor, they are not desired for photolysis . A similar double layer structure was also observed for the LO sample, but the thickness of the compact inner layer was slightly thinner due to the suppression of the thermal oxidation reaction in the low oxygen ambient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cs ignals originated from the adsorbed carbon species onto the surface of the nanostructured materials and are commonly used as ac harge reference for XPS spectra. [31] To confirm the phase structure of the hematite samples before and after annealing, we obtainedX -ray diffraction (XRD) patterns for all samples (Figure 2c), in which all diffraction peaks matched well with those of the rhombohedral a-Fe 2 O 3 (JCPDS No. To further elucidatet his difference, the O1 ss pectra weref itted to three individual peaks to represent different oxygen environments (see the Supporting Information, Figure S1 b-d, Ta ble S1).…”
Section: Resultsmentioning
confidence: 95%